Application of Ergonomic Gymnastics Exercises for Lowering Acid Levels Urinary Tract in Patients with Gout Arthritis With Acute Pain In The Work Area Helvetia Community Health Center, Medan - Lily Putri Marito; Rafika Nur Siregar; Sarabiah Muhammad Samad (International Journal Of Health Science, 2025)
Gout arthritis is a metabolic disorder caused by the accumulation of uric acid crystals in the joints, causing acute pain. One non-pharmacological intervention to reduce uric acid levels is ergonomic exercise. This study aims to determine the effectiveness of ergonomic exercise in reducing uric acid levels in gout arthritis patients. Methods: A descriptive case study design was used in six respondents with gout arthritis and acute pain. The ergonomic exercise intervention was performed three times a week for 20 minutes for one week. Uric acid levels were measured before and after treatment. Results: A significant decrease in uric acid levels was observed in all respondents. Conclusion: Ergonomic exercise is effective in reducing uric acid levels in gout arthritis patients with acute pain.